A benzindole substituted carbazole cyanine dye: a novel targeting fluorescent probe for parallel c-myc G-quadruplexes1. Issue 16 (21st August 2015) - Lin, Dayong; Fei, Xuening; Gu, Yingchun; Wang, Cuihong; Tang, Yalin; Li, Ran; Zhou, Jianguo
<x xml:space="preserve">Abstract</x> Many organic ligands were synthesized to recognize G-quadruplexes.